Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung NRW)

Steuerliches Investitionssofortprogramm: Ausreichender Schritt zur Stärkung des Wirtschaftsstandorts Deutschland? - Giese, Henning; Holtmann, Svea; Koch, Reinald; Langenmayr, Dominika (ifo Schnelldienst)

Investigating the Impact of Conceptual Metaphors on LLM-based NLI through Shapley Interactions - Sengupta, Meghdut; Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Hüllermeier, Eyke; Ghosh, Debanjan; Wachsmuth, Henning (Accepted in Findings)

Fact Checking Knowledge Graphs -- A Survey - Qudus, Umair; Röder, Michael; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (ACM Computing Surveys)
Knowledge graphs are used by a growing number of applications to represent structured data. Hence, evaluating the veracity of assertions in knowledge graphs—dubbed fact checking—is currently a challenge of growing importance. However, manual fact checking is commonly impractical due to the sheer size of knowledge graphs. This paper is a systematic survey of recent works on automatic fact checking with a focus on knowledge graphs. We present recent fact-checking approaches, the varied sources they use as background knowledge, and the features they rely upon. Finally, we draw conclusions pertaining to possible future research directions in fact checking knowledge graphs.
Keywords: fact checking; knowledge graphs; fact-checkers; check worthiness; evidence retrieval; trust; veracity.

Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (Journal of Logic and Computation)
Abstract We study the expressivity and the complexity of various logics in probabilistic team semantics with the Boolean negation. In particular, we study the extension of probabilistic independence logic with the Boolean negation, and a recently introduced logic first-order theory of random variables with probabilistic independence. We give several results that compare the expressivity of these logics with the most studied logics in probabilistic team semantics setting, as well as relating their expressivity to a numerical variant of second-order logic. In addition, we introduce novel entropy atoms and show that the extension of first-order logic by entropy atoms subsumes probabilistic independence logic. Finally, we obtain some results on the complexity of model checking, validity and satisfiability of our logics.

ANTS: Abstractive Entity Summarization in Knowledge Graphs - Firmansyah, Asep Fajar; Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (ESWC2025)
Keywords: firmansyah mousallem ngonga sherif zahera

Facets in Argumentation: A Formal Approach to Argument Significance - Fichte, Johannes; Fröhlich, Nicolas; Hecher, Markus; Lagerkvist, Victor; Mahmood, Yasir; Meier, Arne; Persson, Jonathan (arXiv:2505.10982)
Argumentation is a central subarea of Artificial Intelligence (AI) for modeling and reasoning about arguments. The semantics of abstract argumentation frameworks (AFs) is given by sets of arguments (extensions) and conditions on the relationship between them, such as stable or admissible. Today's solvers implement tasks such as finding extensions, deciding credulous or skeptical acceptance, counting, or enumerating extensions. While these tasks are well charted, the area between decision, counting/enumeration and fine-grained reasoning requires expensive reasoning so far. We introduce a novel concept (facets) for reasoning between decision and enumeration. Facets are arguments that belong to some extensions (credulous) but not to all extensions (skeptical). They are most natural when a user aims to navigate, filter, or comprehend the significance of specific arguments, according to their needs. We study the complexity and show that tasks involving facets are much easier than counting extensions. Finally, we provide an implementation, and conduct experiments to demonstrate feasibility.

Enhancing Pre-Service Teachers' Reflective Competence Through Structured Video Annotation - Rogge, Tim; Herzig, Bardo (education sciences)

Sich in Worte kleiden. Über das Verhältnis von Texten und Textilien - Kraft, Kerstin (Erzählte Mode. Transdisziplinäre Perspektiven auf Text- und Bildgewebe)

Brief Announcement: Efficient Distributed Algorithms for Shape Reduction via Reconfigurable Circuits - Almalki, Nada; Gupta, Siddharth; Michail, Othon; Padalkin, Andreas (4th Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2025, Liverpool, UK, June 9-11, 2025)

Efficient Distributed Algorithms for Shape Reduction via Reconfigurable Circuits - Almalki, Nada; Gupta, Siddharth; Michail, Othon; Padalkin, Andreas (Lecture Notes in Computer Science)

Enlightening release strategies: Accelerated nanoparticle degradation and substance release utilizing light- and pH-responsive polymers - Kramer, Maurice; van der Linde, Matthias; Hönscheid, Lisa; Horky, Corinna; Völlmecke, Katharina; Mulac, Dennis; Herrmann, Fabian; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
To address the challenges associated with poor drug solubility and uncontrolled drug release in conventional dosage forms, a combination of polymer design and advanced drug delivery approaches has been employed. The development of pH-responsive nanoparticles for controlled and selective drug release represents a notable advance in adaptive nanomedicine. This study explores the design of a pH-responsive polymer, poly(1,4-phenyleneacetone dimethylene ketal) (PPADK). Additionally, the incorporation of light-responsive ortho-nitrobenzyl groups (o-NB-PPADK) enhanced the degradation upon exposure to light. Based on the polymer, nanoparticles were prepared using the solvent displacement method. The fluorescence dye Lumogen® Red was incorporated as a model substance. The nanoparticles were characterized by dynamic light scattering to determine their hydrodynamic diameter and size distribution, and the surface charge was analyzed. Atomic force microscopy was used to visualize the surface morphology. The nanoparticles remained stable under physiological pH conditions while exhibiting accelerated degradation and substance release in acidic environment, a property potentially exploitable for tumor targeting. Further enhanced degradation and correspondingly increased release was achieved by incorporating light-responsive elements in the polymer structure. The cytotoxicity of these newly designed nanoparticles was evaluated in cell culture using a breast cancer cell line. These results support the potential of o-NB-PPADK nanoparticles as a possible candidate for selective and effective cancer therapy, combining stimuli-responsive degradation mechanisms for improved therapeutic outcomes.
Keywords: Nanoparticles; Drug delivery; Controlled release; Stimuli-responsiveTumor targeting

Microgel Additives for Aqueous Lubrication: Tailoring Friction and Wear via Composition and Thermal Responsiveness - Syed, Junaid; Dyck, Florian; Herberg, Artjom; Kuckling, Dirk; Gosvami, Nitya Nand (Advanced Engineering Materials)
The tribological behavior of thermo‐responsive poly(N‐isopropylacrylamide) (PNIPAAm)‐based microgels is investigated for use as water‐dispersible lubricant additives. Two types of microgels are synthesized using a surfactant‐free emulsion polymerization method: MG0, consisting of pure PNIPAAm with a volume phase transition temperature (VPTT) of ≈33 °C, and MG16, consisting of PNIPAAm copolymerized with hydrophobic tert‐butyl acrylamide, exhibiting a lower VPTT of around 23 °C. Swelling and lubrication performance are evaluated at 20 and 40 °C. Both microgels significantly reduce friction and wear compared to water alone. At 20 °C, MG0 remains fully swollen and provides effective wear protection through hydrated microgel lubrication. MG16, being near its VPTT, exhibits partial collapse and slightly higher wear. At 40 °C, MG16 demonstrates improved wear resistance, attributed to enhanced film compaction in the collapsed state. Raman spectroscopy and scanning electron microscopy–energy‐dispersive X‐ray spectroscopy confirm that carbon‐rich tribofilms are formed via tribochemical reactions. MG0 produces more graphitic films, while MG16 generates amorphous carbon structures. These findings highlight the tunability of microgel composition for designing adaptive, water‐based lubricants for temperature‐sensitive applications.

Experimental Dataset: Force and Displacement Measurements of Four Rubber-Metal Bushing Types from a Passenger Car under Harmonic Displacement Excitation - Schütte, Jan
This dataset contains experimental measurements of the radial dynamic and quasi-static characteristics of four different types of Rubber-Metal Bushings (RMBs) used in the suspension system of a passenger car under harmonic displacement excitation. For each bushing type, 2–3 individual specimens were tested. Quasi-static measurements were performed at a constant excitation frequency of 0.05 Hz with varying displacement amplitudes. Dynamic measurements were conducted with displacement amplitudes ranging from 0.04 mm to 0.3 mm and excitation frequencies of 2, 5, 10, ..., up to 100 Hz. The data is structured by bushing type, measurement mode, amplitude, and frequency, and is provided in *.csv and *.hrm format. It is intended to support further research in modeling rubber-metal bushings and parameter identification techniques.
Keywords: bushing; experimental data; rubber-metal-bushing; Dataset suspension

The Amelia Project - Episode 87 - King Arthur (537 AD) - Ulsberg Brager, Oystein; Thorne, Philip; Freudinger, Markus
"He came concealed, but he hath now revealed his true identity! Kneel for the mighty King Arthur!" The Amelia Project is a production of Imploding Fictions. This episode featured Alan Burgon as The Interviewer, Hemi Yeroham as Kozlowski, Owen Lindsay as Big Jim, Patrick Lamb as Gavin, Anne Weiner as the barmaid, Anne Marie Sheridan, Beus Lunaire, Lara Bozkurt, Nicola Ségur and Torgny G. Aanderaa as villagers, Jordan Cobb as Jackie Williams and Erin King as Mia Fox. The episode was written by Oystein Ulsberg Brager with story and audio editing by Philip Thorne, translations into Old English by Dr. Markus Freudinger, sound design by Eli Hamada Mcilveen, music by Fredrik Baden, graphic design by Anders Pedersen, production assistance by Maty Parzival, and casting assistance by Julia C. Thorne. The episode was recorded at RedP studio in Vienna, with engineering by Arpad Hadnagy and Oliver Illes and assistance by Paul Kraner. Website: https://ameliapodcast.com/ Transcripts: https://ameliapodcast.com/season-5

Mathematikbezogenes Wissen, Einstellungen und Lerngelegenheiten als Einflussfaktoren der situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachkräfte - Quack, Carolin; Bruns, Julia (Frühe Bildung)

Polymer Suspensions under Uniaxial Extension – A novel Way to Produce Core-Shell-Particles? - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Stärkung sprachlicher Teilhabe durch sprachbildende Praxisanleitung - Hinweise für die Pflegeausbildung aus der Empirie. - Daase, Andrea; Darmann-Finck, Ingrid; Niederhaus, Constanze (Sprache(n) im Beruf: Gestaltung und Förderung beruflicher Sprachbildung an den ver-schiedenen Lernorten)

Menschenmengen extra und intra muros: Die Rolle der Stadtgemeinschaften bei den Gewalttaten des Hirtenkreuzzugs und der Rintfleisch-Verfolgungen - Mersch, Katharina Ulrike (Religiöse Gewalt in historischer Dimension)

Enabling Android Application Monitoring by Characterizing Security-Critical Code Fragments - Eikerling, Hendrik; Kampkötter, Anemone (Lecture Notes in Computer Science)